(untitled) (Actual Problems of Mind, 2022)
This paper attempts to do the following things. First, it reinterprets the notion of “mind engineering” from a more neutral standpoint and offers a totally new approach to the phenomenon. Thus, instead of looking at the phenomenon from a wholly negative perspective (such as identification of mind engineering with “brainwashing,” “mind control” and other manipulatory techniques), it defines mind engineering as the process of “design/redesign, implementation/reimplementation, evaluation/reevaluation of minds.” In itself, this process can be deliberate or forceful. Here, the author looks at deliberate mind engineering primarily. Secondly, the “mind” is defined as a set of beliefs, and the latter, following Charles Peirce, is interpreted as the set of habits. The phenomenon of habit is interpreted pragmatically-hermeneutically and is defined as a “‘fixed’ functional interpretation of the world and one’s place in it that either works or does not work.” If a specific interpretation constantly works, it constitutes a “good” habit. If it does not work, it means a “bad” habit. Unlike the current social-psychological approaches to habit as goal-independent and automatic, and therefore “mindless”/non-cognitive, the author claims that habits are essentially goal-dependent, and cognitive. The habit’s main goal is to resolve the problematic situation that the organism is in. Habit’s cognitive element is grounded in the organism’s interpretive effort that allows it to specify a problematic situation as problematic. Therefore, the connection between the organism and a situation is not direct/immediate but rather is mediated via functional interpretive meaning. In the end, mind engineering must be taken as “habit engineering,” and, thus understood, the phenomenon in question can be seen as one of the key phenomena to clarify human nature.